Critical subaortic stenosis due to fibromuscular ridge in a 66‐year‐old woman: 2D‐3D echocardiography findings. Issue 6 (26th May 2020) - Pergolini, Amedeo; Pingitore, Annachiara; Zampi, Giordano; Pontillo, Daniele; Menafra, Giovanni; Musumeci, Francesco
Abstract: Subvalvular aortic stenosis (SAS) can be either a fixed stenosis resulting from subaortic anatomical obstacle or a dynamic stenosis because of hypertrophic cardiomyopathy. Here, we report a patient with a rare subaortic circumferential fibromuscular tunnel who became unusually symptomatic in her sixth decade of life. Transthoracic and mostly transesophageal echocardiography with 3D application is the preferred diagnostic modality. Indications for surgery include symptoms and LVOT gradient of 50 mm Hg. Our purpose is an image focus on this infrequent case.